A transnational feminist reading of selected Middle Eastern and South Asian chick lit - Bloy, Catherine Susan (Rhodes University, 2026)
This thesis uses a transnational feminist approach to analyse how the selected authors of Middle Eastern and South Asian chick lit explore religion, ethnicity, female friendships, romantic relationships, consumer culture, and the economically independent woman. The thesis considers how the authors’ positions as middle-class, transnational, feminist subjects of the Middle East and South Asia enable them to identify the religious, cultural, and social themes that inform their narratives. I use transnational feminist theory to form the foundation of my reading while integrating the relevant aspects of postfeminist theory as it applies to global chick lit. This approach allows for additional nuance and more intentional engagement with the texts, through which the distinctive elements of the narratives can be recognised. This thesis will consider Almost Single (2013) by Advaita Kala, No Sex in the City (2012) by Randa Abdel-Fattah, Girls of Riyadh (2005) by Rajaa Alsanea, and Ayesha at Last (2018) by Uzma Jalaluddin as representations of Middle Eastern and South Asian chick lit. In my analysis of these novels, I compare and contrast the texts to identify the differences and similarities between transnational and domestic authors and Middle Eastern and South Asian authors and their narratives. In so doing, I explore the form of the novels as they mirror and modify conventions in white Western chick lit. Similarly, I consider the novels’ handling of themes and tropes evident in (most) chick lit and their application in the unique social, economic, and political circumstances of their setting. Middle Eastern and South Asian iterations of chick lit, while similar in formula and conventions, illustrate how authors can utilise the genre to further discourse about feminine subjectivities in their respective locales.
Keywords: Chick lit; Chick lit; Feminism and literature; Transnational feminism; Global South; Genre fiction